Pengaruh kecerdasan emosional terhadap hasil belajar matematika siswa kelas VII MTs - Mauliddin, Mauliddin; Siti Patimah, Siti Patimah (Mathematic Education Departement, State Islamic University of Mataram, 2021)
The purpose of this study was to determine the influence of emotional intelligence on the mathematics learning outcomes of MTs students. NW Pagutan. This type of research is ex-post facto with a quantitative approach. The subjects of this study were seventh grade students at MTs. NW Pagutan. The data collection method used in this research is in the form of questionnaires and documentation. The results obtained in this study are the magnitude of F count is 29,020. Meanwhile, the value of is at a significance level of 5% with N=19, which is 4.45. Then with a significance/probability level of 0.000 < 0.05, meaning that it is significant, so H_a is accepted and H_o is rejected. The conclusion that can be drawn from this research is that there is an influence of emotional intelligence on the mathematics learning outcomes of seventh grade students of MTs NW Pagutan. The suggestions put forward in this study are that teachers are expected to be more familiar with the emotional conditions of students, so that teachers can choose appropriate learning methods or models so that they can help students achieve maximum learning outcomes.